Physical Exercise Restores the Generation of Newborn Neurons in an Animal Model of Chronic Epilepsy - Mendonça, Fabricio N.; Santos, Luiz E. C.; Rodrigues, Antônio M.; Gomes da Silva, Sérgio; Arida, Ricardo M.; da Silveira, Gilcélio A.; Scorza, Fulvio A.; Almeida, Antônio-Carlos G. (Frontiers in Neuroscience, 2017)
Neurogenesis impairment is associated with the chronic phase of the epilepsy in humans and also observed in animal models. Recent studies with animal models have shown that physical exercise is capable of improving neurogenesis in adult subjects, alleviating cognitive impairment and depression. Here, we show that there is a reduction in the generation of newborn granule cells in the dentate gyrus of adult rats subjected to a chronic model of epilepsy during the postnatal period of brain development. We also show that the physical exercise was capable to restore the number of newborn granule cells in this animals to the level observed in the control group. Notably, a larger number of newborn granule cells exhibiting morphological characteristics indicative of correct targeting into the hippocampal circuitry and the absence of basal dendrite projections was also observed in the epileptic animals subjected to physical exercise compared to the epileptic animals. The results described here could represent a positive interference of the physical exercise on the neurogenesis process in subjects with chronic epilepsy. The results may also help to reinterpret the benefits of the exercise in alleviating symptoms of depression and cognitive dysfunction.